Platform transience: changes in Facebook’s policies, procedures, and affordances in global electoral politics - Bridget Barrett; Daniel Kreiss (Internet Policy Review)
This paper presents two case studies of Facebook’s rapid changes relating to international electoral politics: the “I’m a Voter” affordance and the platform’s data and targeting capabilities. The article shows how Facebook changed with respect to its policies, procedures, and affordances, especially given the normative pressure exerted by journalists. Drawing from these case studies, we conceptualise continual and rapid change as “platform transience” and argue that it often arises from external pressure and economic considerations. Platform transience has significant implications for the ability of stakeholders to hold platforms accountable, raises significant issues for electoral fairness, and increases the potential for unequal political information environments.